Toward the Establishment of New Clinical Endpoints for Cystic Fibrosis: The Role of Lung Clearance Index and Cardiopulmonary Exercise Testing - Hatziagorou, Elpis; Kampouras, Asterios; Avramidou, Vasiliki; Toulia, Ilektra; Chrysochoou, Elisavet-Anna; Galogavrou, Maria; Kirvassilis, Fotios; Tsanakas, John (Frontiers in Pediatrics, 2021)
As Cystic Fibrosis (CF) treatment advances, research evidence has highlighted the value and applicability of Lung Clearance Index and Cardiopulmonary Exercise Testing as endpoints for clinical trials. In the context of these new endpoints for CF trials, we have explored the use of these two test outcomes for routine CF care. In this review we have presented the use of these methods in assessing disease severity, disease progression, and the efficacy of new interventions with considerations for future research.